Criminal Law Policy in Combating Corruption in the Digitalization of Public Services Sector - Saptaning Ruju Paminto; Dwi Nurahman; Eriyanto Eriyanto (Journal of Strafvordering Indonesian, 2025)
Digital transformation in public services brings efficiency and transparency, but at the same time gives birth to new modes of corruption that are non-physical, complex, and transnational. Digitalization opens up opportunities for data manipulation, system engineering, and the elimination of traces of electronic transactions, which are difficult to handle with conventional criminal law instruments. Law No. 31 of 1999 and Law No. 20 of 2001 still dominantly use the classic paradigm that focuses on physical state losses, so it is not yet fully able to reach technology-based crimes. The limitations of these norms create legal gaps and the risk of impunity, especially when the principle of legality requires the formulation of clear criminal justices. On the other hand, proving digital corruption requires explicit recognition of electronic evidence, while the judicial system is still based on conventional evidence. This condition emphasizes the need for responsive criminal law reform, both through expanding the formulation of criminal offenses, strengthening the position of electronic evidence, and developing new sanctions relevant to digital crimes. This research uses a normative juridical method by examining positive law, legality principles, doctrines, and law application practices. The analysis shows that the effectiveness of eradicating digital corruption can only be achieved through regulatory harmonization, increasing the technological capacity of the apparatus, and integrating criminal law with the cyber and administrative law regime. Thus, criminal law is required to be adaptive so as not to be left behind from the dynamics of crime in the digital era.